SISTEM SOSIALBUDAYA MASYARAKAT PESISIR Nelayan dan Bakul Ikan di Kampung Tambak Lorok, Kota Semarang - Nurdien H Kistanto (Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
In accordance with the natural environment, namely coastal area, livelihood and employment of many people of Tambak Lorok are fishing, carried out by fishermen as husbands or household heads, and accompanying activities such as processing and selling of marine products, mainly fish, by female fish processors and/or traders. Based on the field data collection and reading the literature, this study analyzes functional interrelationships of fishermen and fish traders in the sociocultural system of Tambak Lorok community in north Semarang City.